Reentrant glass transition leading to ultrastable metallic glass. (April 2020) - Du, Qing; Liu, Xiongjun; Fan, Huiyang; Zeng, Qiaoshi; Wu, Yuan; Wang, Hui; Chatterjee, Debaditya; Ren, Yang; Ke, Yubin; Voyles, Paul M.; Lu, Zhaoping; Ma, Evan
Graphical abstract: Abstract: Polyamorphs are often observed in amorphous matters, and a representative example is the reentrant glass transition in colloid systems. For metallic amorphous alloys, however, the cases reported so far are limited to metallic glasses (MGs) that undergo electronic transitions under gigapascal applied pressure, or the presence of two liquids at the same composition. Here we report the first observation of a reentrant glass transition in MGs. This unusual reentrant glass transition transforms an MG from its as-quenched state (Glass I) to an ultrastable state (Glass II), mediated by the supercooled liquid of Glass I. Specifically, upon heating to above its glass transition temperature under ambient pressure, Glass I first transitions into its supercooled liquid, which then transforms into a new Glass II, accompanied by an exothermic peak in calorimetric scan, together with a precipitous drop in volume, electrical resistance and specific heat, as well as clear evidence of local structural ordering on the short-to-medium-range scale revealed via in-situ synchrotron X-ray scattering. Atomistic simulations indicate enhanced ordering of locally favored motifs to establish correlations in the medium range that resemble those in equilibrium crystalline compounds. The resulting lower-energy Glass II has its own glass transition temperature higher than that of Glass I by as much as 50 degrees. This route thus delivers a thermodynamically and kinetically ultrastable MG that can be easily retained to ambient conditions.